Women on Boards as Moderator of ESG Disclosure, Profitability Toward Company Performance - Nuriza, Vivin; Biduri, Sarwenda; Maryanti, Eny; Hariyanto, Wiwit (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
Company performance serves as a key indicator for assessing a firm's level of success within a specific period, achieved through the synergy of various contributing factors. This study aims to examine the influence of ESG disclosure and profitability on company performance, with the moderating role of women on boards. The research population includes all companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. A total of 215 companies were selected using a purposive sampling technique. The analysis was conducted using SmartPLS 3, employing the outer model to assess the validity and reliability of the constructs, and the inner model to test the research hypotheses. The findings reveal that both ESG disclosure and profitability positively influence company performance. Furthermore, the presence of women on boards enhances the positive effect of ESG disclosure on company performance. However, it does not significantly strengthen the relationship between profitability and company performance.